Precarious Manhood and Its Effects on Aggression: The Role of Cultural Script - Jin, Yuchang (Journal of interpersonal violence, 2021)
The present study tests the precariousness of manhood and the impact of precarious manhood on aggression. In total, 50 undergraduates (25 girls, 25 boys) participated in this experiment. It was found that the male participants used more verbs in the “A man should__” sentence string than in the “One woman should__” sentence string, and similar language patterns were found even after controlling for gender stereotypes. Individuals were found to more often attribute the individual behavior caused by cultural scripts to external situational factors; that is, if individuals agreed that another male’s aggression was due to threatened manhood, this behavior was seen to be because of the male cultural script and was due to external circumstances. To test this view, a total of 56 college students participated in this experiment. In total, 25 college students (11 males, 14 females) took part in the attribution evaluation of two male fighters, and 31 college students (15 males, 16 females) participated in the attribution evaluation of two female fighters. It was found that the male participants believed that other male physical aggression that threatened their manhood was induced by situational factors rather than the internal characteristics of the attacker. The differences between the female participants were not significant, indicating that it was part of the male cultural script for men (rather than women) to defend or restore precarious manhood through aggression.